DNA Barcoding for the Identification of Different HIBISCUS ROSA-SINENSIS Intraspecific Variants using rbcL and ITS2 Markers - Wamahiu Munene, John Mark (2016)
DNA barcoding is a novel technique aimed at providing a means to rapidly and accurately identify species using short, standardized DNA sequences as tags in a fully automatable process. Its usefulness becomes apparent when need arises to support identifications of organisms made in accordance with the existing Linnaean classification system. It is universally applicable to all organisms and only a small set of markers are used. In this experiment, the genetic markers rbcL and ITS2 were used with the aim of assessing their discriminatory powers in as far as differentiating between three varieties of Hibiscus rosa-sinensis namely, Hibiscus rosa-sinenensis el capitolio red, Hibiscus rosa-sinensis red – variegated leaves and Hibiscus rosa-sinenesis pink. Using the Edwards’ method of DNA extraction, genomic DNA was first obtained from the plant samples before the rbcL and ITS 2 gene sequences were isolated from each of the Hibiscus rosa-sinensis variants and amplified by Polymerase Chain Reaction. The PCR products were then sequenced and the sequence data analysed using various bioinformatics tools. The first step of analysis involved sequence editing and quality assessment, followed by BLAST analysis on the NCBI database for sequence comparison. The next step was to conduct Multiple Sequence Alignment in order to detect polymorphisms between the sequences and enable the construction of a phylogenetic tree. Finally, a DNA distance matrix was constructed which allowed for calculation of the barcoding gap and the resulting data was used to distinguish between the three variants of Hibiscus rosa-sinensis. In conclusion, the species discrimination powers of both markers were assessed and although both markers displayed the ability to discriminate between species (interspecific variation), the ITS2 sequence was found to be more suitable for use in the identification of different variants within the species (intraspecific variation) as opposed to the rbcL sequence which was unable to identify differences between interspecies variants.